Study on the Effects of Enzymatic Hydrolysis on the Physical, Functional and Chemical Properties of Peanut Protein Isolates Extracted from Defatted Heat Pressed Peanut Meal Flour (Arachis hypogaea L.) - Kain, Regena Juliana; Chenc, Zhengxing; Abu-Kpawoh, John Christian (Pakistan Journal of Nutrition, 2009)
Physical, chemical and functional properties of peanut protein isolates (HPI) and hydrolysis (HPH) extracted from peanut meal obtained from heat treated peanut oil extraction method were analyzed. HPH exhibited superior functional properties such as whipping, emulsification, fat and water absorption properties. Thermal denaturation profiles indicate that there is no significant difference (p